2002
DOI: 10.1097/00001888-200209000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Medicol

Abstract: Use statistics indicate that over 90% of students regularly use the MEDICOL sites and have found them helpful. University of British Columbia medical school enrollment will increase because of collaborations with campuses and medical centers across the province. MEDICOL will likely play an increased role in distance learning by continuing to deliver the resources already described, as well as facilitating synchronous communications (e.g., PBL chat rooms) and teaching (e.g., video-streamed lectures) to students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Over the last decade medical education has moved away from a traditional didactic, system with lecture-based teaching to more contemporary self-directed learning supported by case-based discussions stimulated by problem-based curricula. More recently, electronic media, such as web-based online supporting material, live streaming of lectures and downloadable applications have emerged as valuable teaching tools [ 1 3 ]. Yet, despite making use of modern platforms, one problem remains the same: these are often passive ways of learning, lacking interactive or integrated assessment elements (of students learning).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade medical education has moved away from a traditional didactic, system with lecture-based teaching to more contemporary self-directed learning supported by case-based discussions stimulated by problem-based curricula. More recently, electronic media, such as web-based online supporting material, live streaming of lectures and downloadable applications have emerged as valuable teaching tools [ 1 3 ]. Yet, despite making use of modern platforms, one problem remains the same: these are often passive ways of learning, lacking interactive or integrated assessment elements (of students learning).…”
Section: Introductionmentioning
confidence: 99%
“…5 Although it is advocated that e-learning can replace traditional methods of teaching, 5,6 it is not suggested that it can substitute supervised sessions with trainers for surgical trainees. 6 Nevertheless, didactic lectures, case-based discussions and small-group discussion can be efficiently replaced by e-learning, 7 through which assessors can track the progress of trainees communicating electronically without time pressures, 8 as well as apply assessments, a significant element in assessing knowledge and skill acquisition. 6 This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…It provides the possibility of interaction of the students with each other and with the lecturer via e-mail and information board, there is also an option to send the students daily tasks . 13 In connection with the conversion of training courses to on-line format a recent problem is to raise motivation and for this purpose problem-oriented training is increasingly applied. In one of the studies this approach contributed to the extending away from the mechanical memorizing of information to the formation of a research thinking in students.…”
Section: Assessment and Discussionmentioning
confidence: 99%